Water Quality Monitoring using ONLIMO Automatic Water Monitoring Device in Water Pollution Monitoring Efforts - Nurlaila, Nurlaila; Asiah, Asiah; Elfidasari, Dewi (Universitas Nasional Jakarta, 2024)
Water quality is one of the key indicators of environmental health that impacts aquatic life and human health. Water quality monitoring is important to measure the impact of human activities and ensure water meets quality standards. Conventional methods of manual water sampling face challenges such as distance, safety risks, and long analysis times, making it less effective for rapid monitoring to address environmental pollution. Following Law No. 32 of 2009, the government requires environmental information for environmental management policies. The Ministry of Environment and Forestry encourages using ONLIMO (online monitoring) technology for automated monitoring, with data published through the MoEF's ONLIMO website. This study was conducted to introduce and analyze the efficiency of ONLIMO technology in water pollution control so that policies and actions can be taken quickly and appropriately. Field verification shows physical factors such as indicators of garbage around the Cipinang River water flow, visible murky watercolor, pungent smelling water, dense residential settlements around the Cipinang River water flow, and the number of industries built in the Cipinang River flow indicate that the Cipinang watershed water quality recorded through ONLIMO water quality monitoring sensors and field verification shows a state of mildly polluted conditions. This factor suggests that the ONLIMO KLHK automatic monitoring tool has the effectiveness and efficiency of water quality monitoring because the data entered into the ONLIMO KLHK database through data loggers and field conditions directly show data similarities. Therefore, the ONLIMO KLHK automatic monitoring tool can be an effective early warning system and allows increased efficiency in water pollution control because the data obtained is real-time and by the original water quality conditions at the location.